Toeplitz operators on generalized Bergman-Hardy spaces - Lusky, Wolfgang (MATHEMATICA SCANDINAVICA, 2001)
We study the Toeplitz operators $T_f: H_2 → H_2$, for $f \in L_∞$, on a class of spaces $H_2$ which in- cludes, among many other examples, the Hardy and Bergman spaces as well as the Fock space. We investigate the space $X$ of those elements $f \in L_∞$ with $\lim_j \|T_f-T_{f_j}\|=0$ where $(f_j)$ is a sequence of vector-valued trigonometric polynomials whose coefficients are radial functions. For these $T_f$ we obtain explicit descriptions of their essential spectra. Moreover, we show that $f \in X$, whenever $T_f$ is compact, and characterize these functions in a simple and straightforward way. Finally, we determine those $f \in L_∞$ where $T_f$ is a Hilbert-Schmidt operator.